Mobile-Integrated Smart School Management Ecosystem Model (SiPPKe) for the Prevention and Intervention of School-Based Violence - Evitha Soraya; Supadi; Tarma; S. Nudia Mastur; Winda Dewi Listyasari (Tadbir : Jurnal Studi Manajemen Pendidikan, 2026)
The escalating prevalence of school-based violence underscores a critical systemic failure in safeguarding student welfare at the secondary level. This research addresses this exigency by developing SiPPKe (School Violence Prevention and Intervention System), an Android-based framework that operationalizes a multi-dimensional approach (encompassing proactive early detection, pedagogical intervention, and a streamlined reporting to resolution protocol) to ensure a responsive, effective, and digitally-integrated institutional environment. The research employed a Research and Development (R&D) approach adapting the Borg and Gall framework, conducted across 48 State Senior High Schools in East Jakarta. The study involved IT management experts alongside quota-sampled teachers and students. The development lifecycle followed five systematic stages: preliminary analysis, initial model construction, expert validation, limited-scale field trials, and large-scale testing with iterative revisions. Data were acquired through a triangulation of literature reviews, interviews, and questionnaires, utilizing descriptive statistics for quantitative analysis and the Miles and Huberman interactive model for qualitative interpretation. Instrument validation confirmed high reliability, while SiPPKe effectively integrated risk mapping, digital education, and rapid-response reporting. Findings reveal that user engagement significantly correlates with TPPK strategy effectiveness. Conclusively, SiPPKe optimizes violence management by streamlining bureaucratic reporting, transforming reactive handling into a proactive, technology-driven safeguarding framework in schools.